GUIDELINES ON THE PREVENTION, DIAGNOSIS, AND TREATMENT OF INFECTIVE ENDOCARDITIS (NEW VERSION 2009) - Gilbert Habib; Bruno Hoen; Pilar Tornos; Franck Thuny; Bernard Prendergast; Isidre Vilacosta; Philippe Moreillon; Manuel de Jesus Antunes; Ulf Thilen; John Lekakis; Maria Lengyel; Ludwig Muller; et al. (Столичная издательская компания, 2016)
Guidelines on the prevention, diagnosis, and treatment of infective endocarditis (new version 2009).